BILINGUAL LEARNING APPROACHES TO IMPROVE ENGLISH LANGUAGE DEVELOPMENT IN ELEMENTARY SCHOOL TEACHER EDUCATION STUDENTS - Siregar, Tiarnita Maria Sarjani Br.; Simanullang, Sri Rahayu; Hutabarat, Aprilia; Munthe, Putri Olivia; Riadi, Kaisyah Abellia (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This study examines the role of bilingual learning approaches in improving English language development among Elementary School Teacher Education (PGSD) students. As future educators, PGSD students are expected to demonstrate adequate English proficiency to support instructional practices, meet curriculum requirements, and integrate bilingual elements in primary school learning environments. This research employs a literature review method by analyzing relevant national and international journals, books, and educational reports that discuss bilingual learning, teacher preparation, and English language development. The findings indicate that bilingual learning approaches contribute significantly to strengthening students’ linguistic competence, particularly in vocabulary development, reading comprehension, speaking confidence, and academic communication skills. Furthermore, the reviewed literature highlights that exposure to bilingual learning environments increases student engagement, motivation, and readiness to apply bilingual instruction in future classrooms. Therefore, integrating bilingual learning approaches is essential for preparing competent, adaptive, and globally oriented future elementary school teachers